Assessment of thermal changes in water buffalo mobilized from the paddock and transported by short journeys - Rodríguez-González, Daniela; Guerrero Legarreta, Isabel; Cruz-Monterrosa, Rosy G.; Napolitano, Fabio; Titto, Cristiane Gonçalves; Abd El-Aziz, Ayman H.; Hernández-Avalos, Ismael; Casas-Alvarado, Alejandro; Domínguez-Oliva, Adriana; Mota-Rojas, Daniel (Frontiers in Veterinary Science, 2023)
Evaluating the welfare of buffaloes during transport is key to obtaining and commercializing high-quality meat products; however, effective assessments require recognizing several stressors that activate physiological mechanisms that can have repercussions on the health and productive performance of species. The aim of this study was to evaluate the surface temperatures of different body and head regions in this species during events prior, and posterior, to transport for short periods; that is, from paddock to loading. The second goal was to determine the level of correlation between thermal windows. This study used infrared thermography (IRT) to evaluate the surface temperature of 624 water buffaloes (Buffalypso breed) during 12 short trips (average duration = 2 h ± 20 min) by focusing on 11 regions of the body (Regio corporis), in the head regions (Regiones capitis) the face regions (Regiones faciei), Orbital region (Regio orbitalis) with special attention to structures such as the lacrimal caruncle, periocular area and lower eyelid (Regio palpebralis inferior); nasal region (Regio nasalis) with special attention to nostril thermal window; and regions of the skull (Regiones cranii) such as auricular region (Regio auricularis) with special attention to auditory canal and frontal–parietal region (Regio frontalis-parietalis) and trunk region (Truncus regionis) such as thoracic and abdominal regions, regions of the vertebral column (Columna vertebralis) with the thoracic vertebral region (Regio vertebralis thoracis) and lumbar region (Regio lumbalis); and regions of the pelvis limb (Regiones membri pelvini). Recordings were made during seven phases: paddock (P1), herding (P2), corral (P3), chute handling (P4), shipping (P5), pre- (P6), and post-transport (P7). A total of 48,048 readings were obtained from 11 thermal windows. The results showed that the surface temperatures of the windows increased by as much as 5°C during P2, P3, P5, P6, and P7 compared to P1 and P4 (p < 0.0001). Differences of at least 1°C were also observed between thermal windows in the craniofacial, lateral corporal, and peripheral zones (p < 0.0001). Finally, a strong positive correlation (r = 0.9, p < 0.0001) was found between the thermal windows. These findings lead to the conclusion that the surface temperature of the craniofacial and corporal regions of buffaloes transported for short periods varied in relation to the phase of mobilization (from paddock to post-transport), likely as a response to stressful factors, since herding and loading increased the thermal values in each window. The second conclusion is that there are strong positive correlations between central and peripheral thermal windows.